Sustainable charcoal value chains support dryland restoration in Ghana - Owusu, M.; Abu, D.; Asante, J. (2020)
To assess how restoration and wood lots might operate in practice, 200 ha of degraded dry forest in Bono East Region, northern Ghana, is being restored through enrichment planting, natural regeneration and agroforestry in five communities.